Subchronic Treatment of Combination Extract Detam 1 Soybean and Jati Belanda Leaves has No Toxic Effect on Function, Weight, and Histopathological of Wistar Rat Kidney - Hidayat, Meilinah; Prahastuti, Sijani; Chikita, Vibiola; Safitri, Dewi; Rahmawati, Siti F.; Soemardji, Andreanus A. (Maranatha Christian University, 2016)
The combination of Detam 1 soybean and Jati Belanda leaves proved to have effect of weight loss. Since it will become longterm using, toxicity effectvresearch is needed.Â This study was conducted to determine the effect of subchronic combination of ethanol extract of soybean Detam 1 (EEDS) and Jati belanda (EEJB) on kidney function, with parameters: urea and creatinine, macroscopic and histopathological of kidney. This study were conducted on 120 Wistar rats (60 males, 60 females), 90 days (treatment group) and 120 days (satellite group). Rats were divided into six treatment groups. Test results of urea and creatinine levels of all treatment groups was lower than control group (p <0.05). The treatment turned out to have a good effect on kidney function. Kidney weight of all groups showed no significant difference with the control group (p> 0.05). Histopathological score interpretationâs result of low dose group male and female kidney rats were not disturbed. In conclusion, the combination of EEDS and EEJBÂ have a good effect on kidney function, didÂ not lead to changes in organ weight and at low doses did not cause disturbance ofÂ renal histopathology.Â Key words: combination of soybean jati Belanda, subchronic treatment, kidney function, kidneyâsÂ weight, kidneyâs histopathology